11th May: 6th Sunday of Easter: Acts 10.44-48; Psalm 98; 1 John 5.1-6; John 15.9-17 - McKenna, Scott S. (The expository times, 2015)
The article presents a sermon idea for Easter which details the meaning of Chapter 10 of the Acts of the Apostles, Psalm 98 and Chapters 5 and 15 of the Book of John. Topics covered include the story of how the apostle Peter was invited to speak in the home of Roman centurion Cornelius as well as the concept of supernatural theism. It discusses how one could feel the Presence of the Holy Spirit.